Mechanisms of pure alexia: spatially based impairment, letter identification deficit, or both? - Bachoud-Lévi A; Bartolomeo P (Neurocase (Taylor & Francis Ltd), 2003)
We studied reading performance for words and for isolated letters in a pure alexic patient. She performed reasonably well when naming isolated letters but was slower in reading letters than a control subject when reaction times (RTs) were recorded. When the patient read isolated letters, RTs were slower for a subset of letters that cannot be recognized from their left part alone (e.g. 'b', an ambiguous letter, could be read 'b' 'h' 'l' or 'k' whereas 'a' has no predictable confounders). We observed a significant positive correlation between the RTs for reading a word and the mean RTs for reading each of its composing letters before its uniqueness point (i.e. the point, when reading from the left to the right, where a word cannot be a word other than the one it is). This result suggests that, in our patient, the letter identification deficit can account for the slow, letter-by-letter reading behaviour, insofar as each letter represents a perceptual problem. Our findings can be accounted for by a deficit in the parallel processing of the left and right parts of each letter, compounded with a bias to process first the left part of the letter, and may thus reconcile the hypotheses of spatially-based deficit (Rapp and Caramazza, 1991) and of a perceptual deficit occurring at the letter identification level (Behrmann and Shallice, 1995; Perri et al., 1996).